ICTV Virus Taxonomy Profile: Secoviridae - Thompson, Jeremy R; Dasgupta, Indranil; Fuchs, Marc; Iwanami, Toru; Karasev, Alexander V; Petrzik, Karel; Sanfaçon, Hélène; Tzanetakis, Ioannis; van der Vlugt, René; Wetzel, Thierry; Yoshikawa, Nobuyuki; Ictv Report Consortium (Journal of general virology, 2017)
Members of the family Secoviridae are non-enveloped viruses with mono- or bipartite (RNA-1 and RNA-2) linear positive-sense ssRNA genomes with the size of the RNAs combined ranging from 9 to 13.7 kb. They are related to picornaviruses and are classified in the order Picornavirales. The majority of known members infect dicotyledonous plants and many are important plant pathogens (e.g. grapevine fanleaf virus and rice tungro spherical virus). This is a summary of the current International Committee on Taxonomy of Viruses (ICTV) report on the taxonomy of the family Secoviridae available at www.ictv.global/report/secoviridae.